Improving the Availability of Unrelated Stem Cell Donors: Evidence from a Major Donor Registry - Michael Haylock; Patrick Kampkötter; Mario Macis; Jürgen Sauter; Susanne Seitz; Robert Slonim; Daniel Wiesen; Alexander H. Schmidt (Institute of Labor Economics (IZA), 2022)
The unavailability of potential stem cell donors poses a critical challenge for donor registries worldwide. This study investigates the impact of initiatives of a stem cell donor registry to enhance donors' availability for confirmatory typing. Initiatives ask donors to provide a sample for genetic analysis and/or information on their temporal unavailability. We analyzed 91,479 confirmatory typing requests from DKMS Germany, a large stem cell donor registry, exploiting a quasi-random initiative assignment based on observable characteristics. We find that, first, invitation to the initiatives increases donors' availability. Intention-to-treat estimates yield effects ranging from 2.5 to 3.2 percentage points, and local average treatment effects estimates range from 3.8 to 8.2 percentage points ( baseline: 77.1%). Second, the difference in availability between participants and non-participants is over 10 percentage points. The initiatives yield a direct positive effect on donor availability and a selection effect through which participation signals a higher commitment.
Keywords: I12; I18; 330; unrelated stem cell donation; donor availability; registry initiatives; sorting; intention-to-treat; local average treatment effects